Hedonisme Dan Kecerdasan Spiritual: Bagaimana Perannya Terhadap Perilaku Keuangan Mahasiswa? - Meo, Febronia Maria Mali; Wutun, Maria B. Mawarni Gelu; Lejap, Hedwigh Hendrikus Temai; Bau Mau, Ignatia Thomasita (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
Positive student financial behavior can increase their prosperity economically. The purpose of this study was to look at the role of students' financial behavior forming such as hedonism and spiritual intelligence. This study uses quantitative methods, with an analysis instrument in the form of multiple linear regression analyzed using SPSS 26. The number of respondents in this study was 94 students of the Faculty of Economics & Business, Widya Mandira Catholic University. The results of this study indicate that hedonism and spiritual intelligence have a significant significant positive and simultaneous significant effect on the financial behavior of students.